Numerical Simulation and Experimental Study on Sealing Performance and Frictional Property of Rotary Lip Seal - Huifang Dong; Jian Hu (Advances in Materials Science and Engineering)
The hydrodynamic theoretical lubrication model of the friction pair between the rotary shaft and the lip seal under the state of full film lubrication was established in this paper. The Reynolds equation was solved by using the finite difference method, and the influence of the viscosity-temperature characteristics of the lubricant was taken into account in the solution process. The distribution of the film thickness and the hydrodynamic pressure in the sealing area was obtained. At the same time, the bench test was carried out and the correctness of the model was verified by comparing the simulation results and test results of reverse pumping rate and friction torque under different rotational speed of the shaft. The microasperity of the lip surface is a necessary condition for achieving the sealing effect. Therefore, the influences of the contact load of the seal and the root mean square deviation of the lip surface on the sealing performance and frictional property were analyzed by using the theoretical model. The analysis results show that the sealing performance and frictional property can be changed by changing the contact load and surface roughness of the lip, but a single increase in the influence of a certain factor cannot achieve good results, and comprehensive consideration is required in product design.